Pelaksanaan Asas Itikad Baik dalam Perjanjian Kredit Secara Lisan dengan jaminan Gadai Mobil - l Gede Surya Mardita Putra; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Jurnal Preferensi Hukum, 2021)
In general, when someone carries out a loan to a bank or company, an agreement will be made that has been agreed by both parties. In this case, there is an agreement but it does not written in the paper. The purpose of this research is to analyze the validity of the oral credit agreement with the car pawn guarantee and the implementation of the good faith principle in the oral credit agreement with the car pawn guarantee. The type of the research used is empirical by using primary data sources and secondary data obtained from field research, literature and legislation relating to the issues. The data collection techniques are carried out by recording and documentation. In order to get a clear explanation, the data is analyzed and presented qualitatively. The result of the research reveals that the credit agreement made orally by Party 1 and Party 2 had fulfilled all the provisions of the validity of the agreement under Article 1320 of the Civil Code. There is an agreement to carry money off by guaranteeing a Toyota car. Party 1 has carried out in good faith the matters agreed in the agreement made together with party 2 without any violation by making repayments of the loan he made to Ketut in the amount of 30% of what was agreed within 5 months with interest on the loan at 10% per month